2002
DOI: 10.1046/j.1365-2141.2002.03593.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of NIPRISAN (Nix‐0699): a naturally occurring, potent antisickling agent

Abstract: Summary. Among the various potential antisickling agents tested, hydroxyurea (HU) has been the most effective compound used for the treatment of patients with sickle cell disease (SCD). Although HU is effective in many patients, not all patients respond to this drug. In addition, some patients reveal adverse effects, including myelosuppression. In an attempt to find other effective agents with less adverse effects, we investigated the antisickling effect of NIPRISAN (Nix-0699). We found that Nix-0699, an ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 19 publications
3
56
0
3
Order By: Relevance
“…97,98 Niprisan inhibits in vitro sickling and increases both the solubility and delay time of solutions of deoxy-HbS, albeit in a highly nonphysiological buffer. 99 Moreover, the extract prolonged the survival of transgenic sickle mice after acute hypoxic challenge. 100 A recent phase 1B dose-escalation study of 26 HbSS and HbS/b 0 -thalassemia patients found that SCD-101 was well tolerated and, at higher doses, it seemed to relieve chronic pain and fatigue but had no impact on Hb levels or hemolysis.…”
Section: Anti-polymerization Drugs Currently In Clinical Trialsmentioning
confidence: 98%
“…97,98 Niprisan inhibits in vitro sickling and increases both the solubility and delay time of solutions of deoxy-HbS, albeit in a highly nonphysiological buffer. 99 Moreover, the extract prolonged the survival of transgenic sickle mice after acute hypoxic challenge. 100 A recent phase 1B dose-escalation study of 26 HbSS and HbS/b 0 -thalassemia patients found that SCD-101 was well tolerated and, at higher doses, it seemed to relieve chronic pain and fatigue but had no impact on Hb levels or hemolysis.…”
Section: Anti-polymerization Drugs Currently In Clinical Trialsmentioning
confidence: 98%
“…Dans certaines régions d'Afrique, les porteurs du trait drépanocytaire représentent jusqu'à 20% de la population avec une prévalence en Afrique Centrale de 25 à 30% (Egunyomi et al, 2009 ;Iyamu et al, 2002 ;Moody et al, 2003 ;Ogunyemi et al, 2008;Voet et Voet, 1998). Deux pourcents de la population en République Démocratique du Congo (RDC) sont touchés par cette maladie, soit plus d'un million de personnes (Mpiana et al, 2012).…”
Section: Introductionunclassified
“…L'utilisation des plantes médicinales semble pourtant ces dernières années donner un peu plus d'espoir. En effet, plusieurs plantes utilisées en médecine traditionnelles africaine contre cette maladie génétique ont montré in vivo l'activité antifalcémiante (Akjie and Fung, 1992 ;Elekwa et al, 2005 ;Iyamu et al, 2002 ;Ibrahim, 2007 ;Egunyomi et al, 2009 ;Ogunyemi et al, 2008).…”
Section: Introductionunclassified
“…These results suggest that the percentage of sickled cells in the peripheral blood decreases after a painful episode. This change was confirmed in transgenic (Tg) sickle mice that were exposed to hypoxia [15][16][17][18]. We previously found that UnExp-blood collected from the antecubital vein of steady-state patients with SCD contains varying percentages of a new type of reversibly sickled cells with blunt edges [1,2].…”
Section: Changes In the Percentage And Morphology Of Sickled Cells Afmentioning
confidence: 91%